Genome-wide characterization of the NLR gene family in tomato (Solanum lycopersicum) and their relatedness to disease resistance - Bashir, Sehrish; Rehman, Nazia; Fakhar Zaman, Fabia; Naeem, Muhammad Kashif; Jamal, Atif; Tellier, Aurélien; Ilyas, Muhammad; Silva Arias, Gustavo Adolfo; Khan, Muhammad Ramzan (Frontiers in Genetics, 2022)
Nucleotide-binding leucine-rich-repeat receptors (NLR), the largest groups of plant disease resistance (R) genes have attracted wide attention due to their crucial role in protecting plants from pathogens. Genome-wide studies of NLRs facilitated by conserved domain based annotated tomato genome. Total 321NLR genes identified in the tomato genome randomly mapped on 12 chromosomes. Phylogenetic analysis and classification of NLRs have revealed 211 genes share afull-length domain categorized into the three major clades CNL, TNL, and RNL and 110 NLRs share partial domain classified in CN, TN, and N with their corresponding motifs and gene structures. Cis-regulatory elements for NLRs exhibit the maximum number of these elements are involved in response to biotic and abiotic stresses, pathogen recognition and resistance. Phylogenetic relationship of tomato NLRs with other species orthologs has shown conservations with Solanaceae members and variations with A.thaliana. Synteny and Ka/Ks analyses of Solanum lycopersicum and Solanum tuberosum orthologs have reflected the importance of the NLRs conservation and diversification from ancestral species million years ago during evolution. RNA-Seq data and qPCR analysis for early and late blight diseases in tomato revealed consistent expression patterns of NLRs. It indicates the up-regulation in infected than control plants with some exceptions and serves as a key regulator for early blight resistance. Moreover, late blight NLRs Solyc04g007060 (NRC4) and Solyc10g008240 (RIB12) expression positively regulatesS.lycopersicum resistance to P.infestans. These findings provide important fundamental knowledge for understanding NLRs evolution and diversity. It will empower the broader characterization of disease resistance genes to be used in pyramiding through speed cloning and developing disease tolerant varieties.